2021
DOI: 10.1093/braincomms/fcab106
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion models reveal white matter microstructural changes with ageing, pathology and cognition

Abstract: White matter microstructure undergoes progressive changes during the lifespan, but the neurobiological underpinnings related to aging and disease remains unclear. We used an advanced diffusion MRI, Neurite Orientation Dispersion and Density Imaging (NODDI), to investigate the microstructural alterations due to demographics, common age-related pathological processes (amyloid, tau, and white matter hyperintensities), and cognition. We also compared NODDI findings to the older Diffusion Tensor Imaging model-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 93 publications
2
40
1
Order By: Relevance
“…Our analyses revealed that the neurite density of the forceps minor was negatively correlated with age, in line with previous reports for fractional anisotropy and mean diffusivity (de Groot et al, 2015), voxelwise neurite density (Merluzzi et al, 2016), and overall diffusion metrics from atlas-based tracts of interest (Raghavan et al, 2021). Neither education nor sex was associated with the neurite density of the forceps minor in the present sample, also in line with previous reports (e.g., Raghavan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analyses revealed that the neurite density of the forceps minor was negatively correlated with age, in line with previous reports for fractional anisotropy and mean diffusivity (de Groot et al, 2015), voxelwise neurite density (Merluzzi et al, 2016), and overall diffusion metrics from atlas-based tracts of interest (Raghavan et al, 2021). Neither education nor sex was associated with the neurite density of the forceps minor in the present sample, also in line with previous reports (e.g., Raghavan et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Aging is associated with a high load of white matter hyperintensities, which tend to accumulate, mostly, in the frontal lobes (Raz et al, 2007). White matter hyperintensities are indicative of small vessel disease (Wardlaw et al, 2015) and have been shown to be associated with lower neurite density of, mainly, corpus callosum (i.e., including the forceps minor) and association (e.g., superior longitudinal fasciculus) fibers (Raghavan et al, 2021). Accordingly, it appears plausible that vascular risk factors or particular age-related vascular damage in frontal regions might contribute to a neurite density reduction in the forceps minor.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason why WMLs regress in SVD over time. In addition, a recent study using neurite orientation dispersion and density imaging demonstrated that increased FW was the strongest predictor of cognitive function in participants in the Mayo Clinic Study of Aging (Raghavan et al, 2021). However, no significant correlations were identified in our SVD study.…”
Section: Discussioncontrasting
confidence: 79%
“…Additionally, previous studies suggested the accuracy of NODDI to assess WM maturation, with NDI being quite sensitive to WM microstructural developmental changes (Batalle et al, 2017; Kimpton et al, 2021). Besides, ODI describes the orientational dispersion of fibers within a tract, which is highly variable across tracts and might change during the maturation of crossing fibers (Raghavan et al, 2021). Nevertheless, additional analyses (not in the scope of this article) might be performed to evaluate the potential correlations between all these metrics, as performed in previous studies (Kunz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%